2023
DOI: 10.1002/advs.202302029
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Engineering M2 Macrophage‐Derived Exosomes Mediate Endoplasmic Reticulum Stress and Immune Reprogramming for Periodontitis Therapy

Abstract: Periodontitis is a chronic infectious disease caused by bacterial irritation. As an essential component of the host immunity, macrophages are highly plastic and play a crucial role in inflammatory response. An appropriate and timely transition from proinflammatory (M1) to anti‐inflammatory (M2) macrophages is indispensable for treating periodontitis. As M2 macrophage‐derived exosomes (M2‐exos) can actively target inflammatory sites and modulate immune microenvironments, M2‐exos can effectively treat periodonti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 52 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…7(a)). 70,71 All the ligatures were removed after 3 weeks of placement, and different hydrogel treatments were injected locally around the maxillary second molar in the rats with CPDM. All the rats were grouped according to treatments assigned at randomization, which were finally separated into four groups, including the diabetes mellitus without chronic periodontitis (DM + NP) group, diabetes mellitus with chronic periodontitis without treatment (DM + P) group, DM + P treated with OPC hydrogel (DM + P-OPC) group and DM + P treated with OPCE hydrogel (DM + P-OPCE) group, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7(a)). 70,71 All the ligatures were removed after 3 weeks of placement, and different hydrogel treatments were injected locally around the maxillary second molar in the rats with CPDM. All the rats were grouped according to treatments assigned at randomization, which were finally separated into four groups, including the diabetes mellitus without chronic periodontitis (DM + NP) group, diabetes mellitus with chronic periodontitis without treatment (DM + P) group, DM + P treated with OPC hydrogel (DM + P-OPC) group and DM + P treated with OPCE hydrogel (DM + P-OPCE) group, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To induce experimental periodontitis, 70,71 SD rats were anesthetized by an intraperitoneal injection of 1% sodium pentobarbital. A 5-0 silk ligature and steel ligature were tied around the maxillary second molar on both sides.…”
Section: Methodsmentioning
confidence: 99%
“…In another study focusing on endometrial injury, Lin et al designed a dynamic PEG hydrogel produced by Ag–S coordination, which dynamically coordinates and merges with ADSC-exos, simulating the endometrial microenvironment to promote neovascularization and tissue regeneration [ 313 ]. There have been few reports on the hydrogel-exosome system in the treatment of myocardial infarction, enteritis, and periodontitis [ [314] , [315] , [316] ]. Therefore, we encourage further exploration of tissues that are currently less researched to fill existing knowledge gaps.…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%
“…Recent research has demonstrated the involvement of M-Exos in the pathological and physiological processes of inflammation and related diseases and have been studied as a potential diagnostic and prognostic markers of Notes: This schematic demonstrates that exosomes can serve as biomarkers (eg miR-155, 67 miR-17, 68 IL-1β, 69 TNF-α 70 ), nucleic acid and protein delivery vehicles (eg BDNF, 71 PPAR-γ, 72 miR-24-3p, 73 miR-370 74 ), drug delivery vehicles (eg berberine, 75 curcumin, 76 melatonin, 77 silibinin 78 ) and the combined strategy of exosome biomaterials (eg The M2 Exo/pDNA/BSP co-delivery system, 79 engineering of BP-loaded HNV 80 inflammation and associated diseases. 65 M-Exos cargoes from different pathological conditions (bacterial infection, viral infection and disease states) may show distinct genomic and proteomic profiles for distinguishing and identifying the diagnosis and development status assessment of different inflammatory stages and different inflammatory diseases, so as to serve as a reference for exploring the pathogenesis of inflammation and related diseases.…”
Section: M-exos Diagnostic Value and Biomarkers To Monitor Inflammati...mentioning
confidence: 99%